Synthesis and Characterization of New Heterocyclic Compounds and Studying the Biological Activity - Wisam Khalifa Jassim (Journal of Global Pharma Technology, 2020)
New series of some of synthesized compounds derived of the compound (2- (5-(3,5-dinitrophenyl)-1,3,4-thiadiazol-2-yl-substituted benzalidine .The starting material was prepared by the reaction of 3,5-dinitro benzoic acid with thiosemicarbazide in presence of POCl3. The derivatives of Schiff bases were prepared by reaction of 2-amino -5-(3,5dinitro phenyl) 1, 3, 4-thiadiazole with appropriate aldehydes (m-nitro, p-N, N-dimethylamino, p-bromo, o-hydroxy, p-hydroxy) benzaldehydes. These Schiff base were synthesized in order to prepare more important compounds which are the quinazolines and oxazepins. These compounds were synthesized from the reaction of Schiff bases (2- 6) with o-amino benzoic acid (anthranilic acid) and phthalic anhydride respectively. The structures of the new compounds were characterized by FT-IR, 1H-NMR spectroscopy besides the melting points and other properties. The biological activity (antibacterial activity) in-vitro are investigated for the derivatives at prepared concentration (1*10-3 M) and showed inhibition ability against growth of the two types of pathogenic bacteria: [Staphylococcus aurous.] as gram positive and [Escherichia coli] as gram negative and showed inhibition ability against bacteria. The most of these compounds are effective against both types of bacteria in varying degree, with high activity for quinazolines and oxazepines. Keywords: Quinazolines, Oxazepines, Biological activity of 1, 3, 4-thiadiazole, Schiff base.